Effects of yoga and mindfulness practices on the autonomous nervous system in primary school children: A non-randomised controlled study - Pune Ivaki; Steffen Schulz; Michael Jeitler; Christian S. Kessler; Andreas Michalsen; Farid I. Kandil; Saskia-Marie Nitzschke; Wiebke Stritter; Andreas Voss; Georg Seifert (Elsevier, 2021)
Objectives: The present study examined the effects of a yoga and mindfulness-based programme on the autonomic nervous system of primary school children by using heart rate variability parameters. Design: A two-arm non-randomised controlled trial compared an integrated yoga and mindfulness-based programme (16 weeks) to conventional primary school lessons. Setting: Primary school classrooms and conference rooms. Interventions: Participants were allocated to a 16-week integrated yoga-based programme or conventional school lessons. A subgroup was randomised to receive 24h electrocardiogram-recordings. Main outcome measures: Heart rate variability indices were measured, both linear (time and frequency domain) and non-linear (symbolic dynamics, compression entropy), calculated from 30-minute extracts of Holter-electrocardiogram-recordings. Assessments were conducted at baseline and at the end of intervention. Results: 40 participants (42.5% female) were included into the analysis of HRV. No significant changes in heart rate variability parameters were observed between the groups after 16 weeks. In the intervention group, a trend towards increased parasympathetic activity could be seen over time, although not significantly enhanced compared to the control group. Conclusion: Results obtained here do not clearly show that children in German primary school settings benefit from an integrated yoga-based intervention. However, exploratory post-hoc analyses point interestingly to an increased nocturnal parasympathetic activity in the intervention group. Further studies are required with high-quality study designs, larger sample sizes and longer-term follow-ups.